2021
DOI: 10.1536/ihj.21-130
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib-Induced Cardiomyopathy in a Patient with Metastatic Non-Small Cell Lung Cancer

Abstract: Erlotinib, an epidermal growth factor receptor tyrosine kinase inhibitor, is a targeted drug used for the treatment of non-small cell lung cancer (NSCLC). Erlotinib is considered relatively safe and generally welltolerated, with rarely reported cardiac side effects. Herein, we report a case of cardiomyopathy that developed during erlotinib treatment for NSCLC. Two months after erlotinib initiation, our 70 year-old female patient complained of progressive dyspnea, and a diagnostic endomyocardial biopsy confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Based on our results, we anticipate that short-term EGFR inhibition can be beneficial in the setting of AC. Furthermore, unlike other EGFR inhibitors, reports of adverse cardiac effects after erlotinib treatment are very rare (Kenigsberg et al, 2017, Stuhlmiller et al, 2017, Barish et al, 2019, Nagashio et al, 2021). Taken together, we conclude that inhibiting EGFR, thereby enhancing desmosome assembly via ROCK stabilizes desmosome integrity and cardiomyocyte cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we anticipate that short-term EGFR inhibition can be beneficial in the setting of AC. Furthermore, unlike other EGFR inhibitors, reports of adverse cardiac effects after erlotinib treatment are very rare (Kenigsberg et al, 2017, Stuhlmiller et al, 2017, Barish et al, 2019, Nagashio et al, 2021). Taken together, we conclude that inhibiting EGFR, thereby enhancing desmosome assembly via ROCK stabilizes desmosome integrity and cardiomyocyte cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we anticipate that EGFR inhibition can be beneficial in the setting of AC. Furthermore, unlike other EGFR inhibitors, reports of adverse cardiac effects after erlotinib treatment are very rare ( 16 , 73 75 ). Taken together, we conclude that inhibiting EGFR, thereby enhancing desmosome assembly via ROCK, stabilizes desmosome integrity and cardiomyocyte cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…Pinquie et al ( 18) also reported a new case of dilated cardiomyopathy associated with erlotinib therapy, suggesting that long-term maintenance therapy with erlotinib may cause dilated cardiomyopathy. Kenji et al (19) report a case of cardiomyopathy that developed during erlotinib treatment for NSCLC. Two months after erlotinib initiation, our 70year-old female patient complained of progressive dyspnea, and a diagnostic endomyocardial biopsy confirmed non-specific cardiomyopathy, indicating erlotinib-induced cardiomyopathy.…”
Section: Erlotinibmentioning
confidence: 99%
“…Kenji et al. ( 19 ) report a case of cardiomyopathy that developed during erlotinib treatment for NSCLC. Two months after erlotinib initiation, our 70-year-old female patient complained of progressive dyspnea, and a diagnostic endomyocardial biopsy confirmed non-specific cardiomyopathy, indicating erlotinib-induced cardiomyopathy.…”
Section: Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%